Pressure retarded osmosis: Advancement, challenges and potential. (April 2021) - AlZainati, Nahawand; Saleem, Haleema; Altaee, Ali; Zaidi, Syed Javaid; Mohsen, Marwa; Hawari, Alaa; Millar, Graeme J.
Highlights: Pressure retarded osmosis membrane is available although there is a shortage of pilot plant tests. RO brine-wastewater has a great potential for power generation in PRO process. Salinity gradient resource should be selected to reduce the energy requirements for Pretreatment. Dual-stage PRO process has the potential to increase the power generation as an emerging technique. Abstract: An excessive amount of renewable energy could be possibly produced when solutions of dissimilar salinities are combined simultaneously in a semipermeable membrane. The aforestated energy harnessing for transformation into power could be achieved through the pressure retarded osmosis (PRO) process. The PRO system utilizes a semipermeable membrane for separating a low concentration solution from a pressurized-high concentrated solution. This work examines the recent developments and applications of the PRO process and potential energy that could be conceivably harvested from salinity gradient resources in a single-stage and multi-stage PRO processes. One of the existing challenges for this process is finding a commercial membrane that combines characteristics of the forward osmosis membrane (for reducing the phenomenon of concentration polarization) and the reverse osmosis membrane (to withstand high hydraulic pressure). For addressing this challenge, details about the commercial PRO membranes and the innovative laboratory fabricated PRO membranes are introduced. The potential of the PRO process is presented by elucidating salinity gradient resources, the energy of Pretreatment, the process design, PRO-desalination systems, and dual-stage PRO (DSPRO). It is anticipated that this paper can assist in widely understanding the PRO process and thus deliver important data for activating additional research and development.